2007
DOI: 10.1203/01.pdr.0000250207.95723.96
|View full text |Cite
|
Sign up to set email alerts
|

IP-10 Is an Early Diagnostic Marker for Identification of Late-Onset Bacterial Infection in Preterm Infants

Abstract: Very low birth weight (VLBW) infants with suspected late-onset infection requiring sepsis screening were enrolled in a prospective study to evaluate the diagnostic utilities of a comprehensive panel of key chemokines and cytokines, both individually and in combination, to identify diagnostic markers for early recognition of bacterial sepsis and necrotizing enterocolitis (NEC). Plasma chemokines interleukin (IL)-8, interferon-␥-inducible protein 10 (IP-10), monokine induced by interferon-␥ (MIG), monocyte chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
124
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(139 citation statements)
references
References 31 publications
7
124
1
7
Order By: Relevance
“…Higher levels of IP-10 may be detected in sepsis, severe sepsis and septic shock groups compared with systemic inflammatory response syndrome (37). High levels of IP-10 have previously been detected in preterm infants with bacterial infection (12). Although bacterial and viral infection induce IP-10 level, the highest levels of IP-10 in the present study were observed among influenza virus, culture-negative and culture-positive groups (data not shown).…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…Higher levels of IP-10 may be detected in sepsis, severe sepsis and septic shock groups compared with systemic inflammatory response syndrome (37). High levels of IP-10 have previously been detected in preterm infants with bacterial infection (12). Although bacterial and viral infection induce IP-10 level, the highest levels of IP-10 in the present study were observed among influenza virus, culture-negative and culture-positive groups (data not shown).…”
Section: Discussionsupporting
confidence: 45%
“…Culture-negative state is a commonly observed in patients diagnosed with sepsis (11)(12)(13)(14)(15). In the present study, serum CRP levels and WBC counts were sensitive and reliable indexes for distinguishing bacterial infection from viral infection.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…A series of papers have demonstrated that unstimulated IP-10 levels in blood or plasma are increased with infection and disease, such as TB [101][102][103][104], hepatitis C viral infection [105][106][107] and bacteremia [108][109][110]. IP-10 is produced at the site of inflammation and the levels in the blood appear to correlate with the extent of the inflammatory process.…”
Section: Other Potential Uses Of Ip-10 In Tb Managementmentioning
confidence: 99%